If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -2 = 3a + 4 Reorder the terms: -2 + 5a = 3a + 4 Reorder the terms: -2 + 5a = 4 + 3a Solving -2 + 5a = 4 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -2 + 5a + -3a = 4 + 3a + -3a Combine like terms: 5a + -3a = 2a -2 + 2a = 4 + 3a + -3a Combine like terms: 3a + -3a = 0 -2 + 2a = 4 + 0 -2 + 2a = 4 Add '2' to each side of the equation. -2 + 2 + 2a = 4 + 2 Combine like terms: -2 + 2 = 0 0 + 2a = 4 + 2 2a = 4 + 2 Combine like terms: 4 + 2 = 6 2a = 6 Divide each side by '2'. a = 3 Simplifying a = 3
| 2(x-4)+12=x-4(6+2x)+9x | | 12×-1/3 | | 13=10 | | 3log(2)x=28 | | -53/4-31/2= | | 4x-40=13-6x+3 | | 2y-10x=10 | | 3.50x=10.50 | | 3x^2+10=100 | | 2x+7=15+4x | | 2x+12+9=x+3 | | 6x+5+9x-10+80+90=360 | | X+6=-8x+5 | | (x^2+0.8)(x^2+0.8)= | | 3x-29=17-5x | | 18=9+3h | | 7tanx+2=9 | | 3y+6-2=8-2y | | 7/3*8/6 | | -4/7y16 | | 12=15-3p | | 2(x-4)+12=x-4(6+2x)+9 | | 42r^2-35r=0 | | -5+1y=-8x | | 15=2v+3 | | 9p-4q=-15 | | 8=10-2r | | -6x+3=-6x-5 | | 4x+7x-8=-19 | | 40=5e | | 3x^2+7=301 | | 5+2x=3x+-4 |